THE VARIETY SPECIES OF WATERBIRDS IN REGION WETLAND AT VILLAGE SUNGAI RASAU SUBDISTRICT BUMI MAKMUR DISTRICT TANAH LAUT AS MATERIAL ENRICHMENT IN THE FORM OF HANDOUT COURSES OF ZOOLOGI VERTEBRATE - Mahrudin Mahrudin; Muhammad Arsyad (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2018)
Biodiversity in some region are the local potential that can developed in support learning in school or college, can be either teaching material. The potential of based on local need to develop so the learners more understand the object of studied superior Biology learning who has a relate with living creatures. Various of learning material in learning wich one is handout . bird is a live object in variety of habiats, in land or waters (water bird), wherethe wetland is one of habitats, provide resources and place for bird. The development of teaching materials based on local doing for increase of comprehension and learning outcomes of students. Sungai Rasau is one of wetland in Kalimantan Selatan can be habitats for birds especially waterbird. This research purpose to analyze variety of waterbirds in region wetland village Sungai Rasau Kecamatan Bumi makmur district Tanah laut and analyze the validity of handout compiled from result of research. The kind of research used are descriptif and developed up to the stage of test readability. The result of researchshowed for the species of waterbirds found there are 21 types includes in 7 family. While handout courses of zoology vertebrate develop from result of research include in categories very valid.